Local Expenditures, Local Wealth, Financial Management Accountability, and Local Government Administration Performance: Empirical Studies in Indonesia - Muhtar Muhtar (University of Merdeka Malang, 2022)
This study attempts to obtain empirical evidence regarding the determinants of local government administration performance in Indonesia using the local expenditures, local wealth, and financial management accountability factors. The research uses secondary data obtained from authorized government agencies. Through purposive sampling selection, this study generates 1987 observations from 508 Indonesian local governments within the 2015-2018 period, analyzed with multiple linear regression. The findings from our analysis demonstrate that the local government administration performance in Indonesia on average has reached a high level despite there still exists a number of local governments with medium and low performance. Multiple linear regression analysis generates empirical findings that operational expenditures, regional wealth, and financial management accountability exhibit a positive effect towards local government administration performance. However, capital expenditures does not show any significant effect. Further robustness testing also produced consistent findings for all independent variables. This study provides recommendations for realization of local governments to continuously improve the effectiveness of local expenditures, both operating expenditures and capital expenditures. The realization of capital expenditures must be followed by proper utilization of fixed assets to produce the expected outcomes. Local governments must also continue to maximize the local potential while maintaining good local financial accountability for the sake of improving local government administration performance.